An investigation on the stimulated salivary flow rate in menopause and post menopause women - Aghahosseini F. Associate Professor; Akhavan Karbasi MH. Assistant Professor (Tehran University of Medical Sciences, 2003)
Statement of Problem: Menopause can exert extensive somatic and psychological effects on women at this stage including: oral complaints such as dry mouth, glossodynia, viscous saliva, although these findings should be studied further."nPurpose: The aim of this study was to investigate the stimulated salivary flow rate of 158 menopause and post menopause women."nMaterial and Methods: In this cross- sectional and analytic- descriptive study, 158 women, at post menopause stage, were selected as case group. The controls consisted of 83 same aged men. None of the subjects had any systemic disease and did not use any drugs. Age range, in both groups, was 50-69 years old. Psychical condition of two groups, were compared by HADSCALE test. Oral symptoms were also compared and evaluated. In order to analyze the results, "t" and "Mann- Whitney" tests were used. Results: No significant difference was found between two groups regarding the quantity of stimulated saliva and psychological condition, but the incidence of oral symptoms in case group was significantly higher than the control group (P=0.002)."nConclusion: Based on this study, although oral symptoms have a significant relation with menopause, can not be attributed to the quantity of saliva or psychical condition. In order to find the underlying reasons, more investigations should be performed on quality changes of saliva or other factors.